2018
DOI: 10.1016/j.ultsonch.2017.06.029
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ultrasonic agitation on supercritical CO2 copper electroplating

Abstract: Applying ultrasound to the electroplating process can improve mechanical properties and surface roughness of the coating. Supercritical electroplating process can refine grain to improve the surface roughness and hardness. However, so far there is no research combining the above two processes to explore its effect on the coating. This study aims to use ultrasound (42kHz) in supercritical CO (SC-CO) electroplating process to investigate the effect of ultrasonic powers and supercritical pressures on the properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Notably, the observed diffraction pattern in US-SC-CO 2 -15 W cm −2 displays the most significant full width at half maximum (FWHM), which indicated that ultrasonic agitation would lead to the smallest grain size [16] , [23] , [24] . Similar to the previous reports, the grain sizes are calculated from the Scherrer equation [38] , [39] , [40] , [41] , [42] . The calculated average grain size values are presented in Fig.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Notably, the observed diffraction pattern in US-SC-CO 2 -15 W cm −2 displays the most significant full width at half maximum (FWHM), which indicated that ultrasonic agitation would lead to the smallest grain size [16] , [23] , [24] . Similar to the previous reports, the grain sizes are calculated from the Scherrer equation [38] , [39] , [40] , [41] , [42] . The calculated average grain size values are presented in Fig.…”
Section: Resultsmentioning
confidence: 84%
“…The observed result confirms that ultrasonic power utilization enhances the electrocatalytic activity due to reducing the diffusion layer’s thickness and raising mass-transport of electroactive substances to the electrode surface. The combination of ultrasonic agitation with SC-CO 2 further accelerates the metal ions in the electrolyte through the soft cavitation behavior, resulting in a homogenous distribution of ions and increased active site species on the grain boundary [38] , [39] . In contrast, a further increase in the ultrasonic power (30 W cm −2 ) reduces the Cu film’s electrocatalytic performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase could be due to that the particles coming from the CO 2 arrive on the surface, and it is acting as a coalescence point for larger grain growth (grain refinement effect). 43 At sample S4, a changed abrupt is presented; the roughness increases approximately 15.7 times concerning the S1 and S2 samples. These could be because the CO 2 gases produce microbubbles on the surface.…”
Section: Results and Analysismentioning
confidence: 90%
“…Meanwhile that in the S3 sample, the roughness increases two times (3.14 nm) concerning the S1 and S2 samples. This increase could be due to that the particles coming from the CO 2 arrive on the surface, and it is acting as a coalescence point for larger grain growth (grain refinement effect) 43 . At sample S4, a changed abrupt is presented; the roughness increases approximately 15.7 times concerning the S1 and S2 samples.…”
Section: Results and Analysismentioning
confidence: 95%